Elucidation Of Pha Biosynthesis Regulatory Elements In Pseudomonas Sp. Usm4-55 - Hasan, Kamariah (2013)
PHA synthases are the key enzymes for bioplastic production in bacteria. To determine regulators of PHA synthase genes, a library of insertional mutants of Pseudomonas sp. USM4-55 by mini-Tn5 was generated. Transcriptional fusion constructs containing the lacZ within phaC1 and phaC2 genes of Pseudomonas sp. USM4-55 were used in this study. Five phaC1 over-expressed mutants were successfully isolated and none for phaC2. The mini-Tn5 insertions were found to be located on genes encoding these proteins: anti-sigma factor K, a protein translocase subunit (SecB), an ATP dependent protease (Lon) and PhaF (PHA granule associated protein). By inserting a gmR gene, the secB and lon genes were knocked out in the wild type Pseudomonas sp. USM 4-55 as well as its derivatives which contained a transcriptionally-fused lacZ gene within the phaC1 and phaC2 genes (Pseudomonas sp. USM LZC1 and Pseudomonas sp. USM LZC2, respectively). The SecB¯ and Lon¯ mutants in Pseudomonas sp. USM LZC1 showed an over-expression of lacZ as similarly shown by the original mutants indicating that these genes indeed play a role in phaC1 regulation. To study gene expression, real time qRT-PCR was performed in the SecB¯ and Lon¯ mutants of Pseudomonas sp. USM4-55. The phaC expression levels of these mutant strains were up regulated at log phase but were down regulated at stationary phase compared to the wild type. In physiological studies, the SecB¯ strain increased PHA production by 50% and 75% when grown in defined medium supplemented with palm fatty acid distillate (PFAD) and glucose, respectively, as a carbon source relative to the wild type.